Nature sports participation: Understanding demand, practice profile, motivations and constraints - Melo, Ricardo (2017)
Nature sports is a sports field associated with active sport tourism and is one of the fastest growing segments of the tourism industry. Even though nature sports are economically very significant, little is known about participants and their participatory behaviour. Thus, a study was conducted using a convenient sample of 1126 nature sports participants to understand their socio-demographic characteristics, demand profile, practice behaviours, motivations and constraints. The results indicate that nature sports participants are mainly young males, with higher education, highly-qualified jobs and high income. The nature sports activity that most of the surveyed individuals already practice is MTB. This is also the activity practiced more frequently by more individuals, and the activity most individuals would like to practice more often. Nature and adventure are indicated as the main reasons for practicing nature sports, while lack of time and lack of money are the main constraints for participation. Statistical tests also revealed significant statistical differences in participation between the different nature sports activities. These data allow augmenting the management and marketing intelligence for owners and managers of nature sports-related businesses as well as agencies and organizations promoting nature sports (tourism). Policy implications for nature sports are also discussed.